Recurrent Early Thrombus Formation in HeartMate II Left Ventricular Assist Device - Massimo Capoccia MD, MSc; Christopher T. Bowles PhD; Anton Sabashnikov MD; Andre Simon MD, PhD (SAGE Publishing, 2013)
Left ventricular assist devices are becoming an established treatment for end-stage heart failure. In spite of their proven benefit, pump thrombosis remains a significant complication. Here we describe the challenging management of a patient with recurrent pump thrombosis.